Prenatal diagnosis of a 14-Mb 11p11.2-p13 deletion by chromosome microarray analysis in a pregnancy with fetal recombinant chromosome 11 syndrome of rec(11)del(11)(p11.2p13)ins(11)(q21p11.2p13) and maternal intrachromosomal insertion of ins(11)(q21p11.2p13) - Chih-Ping Chen; Chen-Yu Chen; Fang-Tzu Wu; Peih-Shan Wu; Yen-Ting Pan; Chen-Chi Lee; Wen-Lin Chen; Wayseen Wang (Elsevier, 2024)
Objective: We present prenatal diagnosis of a 14-Mb 11p11.2-p13 deletion by chromosome microarray analysis (CMA) in a pregnancy with fetal recombinant chromosome 11 syndrome of rec(11)del(11) (p11.2p13)ins(11) (q21p11.2p13) and maternal intrachromosomal insertion of ins(11) (q21p11.2p13). Case Report: A 25-year-old, primigravid woman underwent amniocentesis at 17 weeks of gestation because of a family history of psychiatric disorders in her two brothers and one maternal uncle. Array comparative genomic hybridization (aCGH) analysis of amniocentesis revealed a 14-Mb 11p13p11.2 deletion. The pregnancy was terminated at 19 weeks of gestation, and a 252-g fetus was delivered. Cytogenetic analysis of the parental bloods and cord blood revealed a karyotype of 46,XX,ins(11) (q21p11.2p13) in the mother, 46,XY in the father and 46,XY,rec(11)del(11) (p11.2p13)ins(11) (q21p11.2p13) in the fetus. aCGH analysis on the DNA extracted from cord blood revealed the result of arr 11p13q11.2 (32,697,424-46,712,173) × 1.0 [GRCh37] with a 14-Mb deletion of 11p13-p11.2 encompassing 54 OMIM genes including PHF21A, ALX4, EXT2 and SLC1A2. Polymorphic DNA marker analysis showed a maternal origin of the 11p deletion. The present case had an 11p13-p11.2 deletion encompassing 11p12-p11.3 which is associated with Potocki-Shaffer syndrome (PSS) or chromosome 11p11.2 deletion syndrome. Conclusion: CMA is useful for prenatal detection of fetal genomic imbalance in case of familial intrachromosomal insertion.